Life and Labor on the Border Working People of Northeastern Sonora, Mexico, 1886-1986 - Heyman, Josiah (University of Arizona Press, 1991)
For thousands of Mexican laborers, life along the U.S. border represents an opportunity both to earn wages and to gain access to consumer goods. For anthropologist Josiah Heyman, this labor force presents an opportunity to gain a better understanding of working people, "to uncover the order underlying the history of waged lives." Life and Labor on the Border traces the development of the urban working class in northern Sonora over the period of a century. Drawing on an extensive collection of life histories, Heyman describes what has happened to families over several generations as people have left the countryside to work for American-owned companies in northern Sonora or to cross the border to find other employment. Heyman searches for the origins of "working classness" in these family histories, revealing aspects of life that strengthen people's involvement with a consumer economy, including the role of everyday objects like sewing machines, cars, and stoves. He considers the consequences of changing political and economic tides, as well as the effects on family life of the new role of women in the labor force. Within the broad sweep of family chronicles, key junctures in individual lives-both personal and historical crises-offer additional insights into social class dynamics. These life stories convey the positive sense of people's goals in life and reveal the origins of a distinctive way of life in the borderlands.